Bacteria Fauna from the House Fly, Musca domestica (L.) - Nazni, W.A.; Seleena, B.; Lee, H.L.; Jeffery, J.; Rogayah, T.A.R.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2005)
The house fly, Musca domestica has long been considered a potential agent for disease transmission ever since its existence. The general truth of this assertion remains undisputed till the present day in spite of increasing awareness toward an improved sanitation and better hygiene. The habitual movement of house fly from filthy substrata such as human faeces, animal excreta, carcasses, garbage, etc. makes them ideal candidates for disease transmission such as cholera, shigellosis, salmonellosis and others when settling on food. Fly as a potential mechanical vector of pathogenic bacteria was elucidated in this study by examining flies from various breeding sites such as food courts, dumping ground, food processing areas and poultry farm in Peninsular Malaysia. The flies were baited with 10 sugar solution on a glass slide in the field. All materials used for collection of samples were sterile. Bacteria from fly sample were isolated using the normal isolation technique. Bacillus sp., Coccobacillus sp., Staphylococcus sp., Microccus sp., Streptococcus sp., Acinetobacter sp., Enterobacter sp., Proteus sp., Escherichia sp., Klebsiella sp. and yeast cells were isolated from feaces, vomitus, external surfaces and internal organs of house fly. Newly emerged house fly did not harbour any bacteria.